The Relationships between Cholesterol and Suicide: An Update. (23rd December 2012) - De Berardis, Domenico; Marini, Stefano; Piersanti, Monica; Cavuto, Marilde; Perna, Giampaolo; Valchera, Alessandro; Mazza, Monica; Fornaro, Michele; Iasevoli, Felice; Martinotti, Giovanni; Di Giannantonio, Massimo
Abstract : Cholesterol is a core component of the central nervous system, essential for the cell membrane stability and the correct functioning of neurotransmission. It has been observed that cholesterol may be somewhat associated with suicidal behaviours. Therefore, the aim of this paper was to elucidate current facts and views about the role of cholesterol levels in mood disorders. The majority of the studies reviewed in the present paper suggest an interesting relationship between cholesterol (especially lower levels) and suicidality. On the other hand, particularly during the last years, relationships between serum cholesterol and suicidality were doubted on the basis of some recent studies that have not found any correlation. However, the debate on relationships between cholesterol and suicide is open and longitudinal studies on a larger sample of patients are needed to further clarify this important issue.